In vitro antibacterial activity on human pathogenic bacteria and larvicidal effect of root from Hemidesmus indicus (Linn.) on Culex qinquifasciatus - S. Sujatha,; Anusha J.R, (International Journal of Phytomedicine, 2010)
The present study was undertaken to evaluate the effect of extraction from Hemidesmus indicus roots on five different solvents activity against the pathogenic and non-pathogenic organisms also larvae of the Culex qinquifasciatus mosquito. H. indicus (L.) is one of the plants used in Ayurveda for several remedies it belongs to the family Asclepiadaceae. The experimental roots were tested for their phytochemical constituents and antimicrobial activity against 15 human pathogenic microorganisms using standard disc diffusion method. Moreover, the methanol and petroleum ether extracts were active against most of the tested organisms as they showed potential phytochemical constituents. The antimicrobial activities of the extracts were compared with their respective reference antibiotics as minimum inhibitory concentrations (MICs). Apart from petroleum ether, all other solvent extracts such as ethanol, methanol, chloroform and aqueous extract showed significant results. Among the 12 bacterial species maximum inhibition zone was 16.00±0.18, 10.65±0.19 and 16.3±0.20 observed the following bacteria such as E.coli, P. mirabilis and S. typhimurium respectively. The larvicidal effect of aqueous extracts of H. indicus roots were tested against Culex quinquefasciatus larvae at the concentrations of 1, 2, 3, 4 and 5% upto three days. Larval mortality was 100% with the use of 5% concentration of root aqueous extract after 2 days was observed. It is suggested that the aqueous extract of Hemidesmus indicus can be used as natural insecticide for mosquito control.